ANALISIS STRUKTUR MODAL YANG OPTIMAL PADA PT. TELEKOMUNIKASI INDONESIA, Tbk PERIODE 2004-2008 - Arnold Japutra; Winda Wijaya (Business Management Journal, 2017)
Capital structure is one of the most important elements in a company. Decision-making errors in the capital structure may cause a very big impact and it can force the company into bankruptcy. Therefore, in order to continue operating, a company should have an optimal capital structure. Optimal capital structure is achieved at the lowest cost level and the highest level return on equity. The research objective is to measure the financial performance of PT Telekomunikasi Indonesia, Tbk by analyzing the composition of capital structure, ACC, ROE, and whether the capital structure by the years 2004-2008 were optimal or not. From the results of the research, capital structure of PT Telekomonikasi Indonesia, Tbk during the years 2004 -2008 showed an optimal capital structure. The result can be seen as the ROE produced by the company is bigger compared to Weighted Average Cost of Capital (WACC) for each period.Key words : Capital structure, return on equity, Weighted Average Cost of Capital